2021
DOI: 10.14710/ijred.2022.41116
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Improvement of Ground-Mounted Solar Power Generation in Agrivoltaic System by Cultivation of Bok Choy (Brassica rapa subsp. chinensis L.) Under the Panels

Abstract: An agrivoltaic system is a combination of solar power generation and crop production that has the potential to increase the value of land. The system was carried out at a 25-kW photovoltaic (PV) power plant located at the Asian Development College for Community Economy and Technology (adiCET), Chiang Mai Rajabhat University, Thailand. The growth and yield of bok choy (Brassica rapa subsp. chinensis L.) and the solar power output were investigated and compared with the control. Moreover, the efficiency of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The authors also discovered that the plants cultivated under the SPV roof were shorter than their counterparts. Kumpanalaisatit et al (2022) made the same observation and discovered that the pak choi plants cultivated in an agrivoltaic system were shorter and had fewer leaves compared with their counterparts.…”
Section: Effect Of Solar Module Shade On Yieldmentioning
confidence: 79%
See 1 more Smart Citation
“…The authors also discovered that the plants cultivated under the SPV roof were shorter than their counterparts. Kumpanalaisatit et al (2022) made the same observation and discovered that the pak choi plants cultivated in an agrivoltaic system were shorter and had fewer leaves compared with their counterparts.…”
Section: Effect Of Solar Module Shade On Yieldmentioning
confidence: 79%
“…Therefore, they concluded that the light intensity under the SPV roof was suitable for the growth of pak choi. Furthermore, Kumpanalaisatit et al (2022) cultivated pak choi in ground-mounted agrivoltaic facilities with higher shading. They reported that the yield of pak choi in such facilities was 92% lower than that of the control group because the solar modules were closer to the ground and the shading rate was higher.…”
Section: Effect Of Solar Module Shade On Yieldmentioning
confidence: 99%
“…A solar-based photovoltaic (PV) energy system is the most common form of renewable energy source, having a huge presence in energy markets. , This is because the Sun’s continuous solar energy of 1367 W/m 2 is distributed throughout the atmosphere. The total amount of energy absorbed by the planet from solar radiation at any instance is estimated as 1.8 × 10 11 MW .…”
Section: Machine Learning For Rementioning
confidence: 99%
“…The solar power output and development of Brassica rapa subsp. Chinensis L. at a 25-kW PV power plant was compared to the control by Manoch Kumpanalaisatit et al (Kumpanalaisatit et al 2022) With a crop yield of 2.28 kW, the PV generated the most electricity. Ruth Anne Gonocruz et al (Gonocruz et al 2021) studied a variety of factors that affect rice crop yield, including fertiliser application, temperature, and solar radiation, all of which were directly observed and evaluated to see if changes were linked to PV systems erected above rice farms.…”
Section: Greenhouse Agrivoltaics In Protected Cultivationmentioning
confidence: 99%